BERSAUDARA Robot (Room And Air Cleaner) As a Preven-tion of the Spread of Viruses in Work Areas in Buildings and Isolation Rooms - Agus Siswoyo; Eko Aris Cahyono; Rodik Wahyu Indrawan (MBI, 2023)
BERSAUDARA Robot innovation emerged based on health protocols in the new normal era and workers' anxiety about the spread of viruses in buildings. This robot is designed by utilizing the development of robotics technology, Remote Operated Vehicle (ROV), vacuum floor cleaner, and air purifier equipped with UV Sterilizer and HEPA Filter. BERSAUDARA Robot innovation is expected to fulfill the protocol for preventing the spread of the Covid-19 virus, especially work areas in buildings or isolation rooms, by cleaning floors and air regularly so as to minimize human contact and support the continuity of the activities of workers during the